KONSEP DIRI ADVERSITY QUOTIENT DAN KEMANDIRIAN BELAJAR SISWA - Hairina Novilita; Suharnan Suharnan (Jurnal Psikologi Tabularasa, 2013)
This research was conducted aiming to determine whether there is a relationship between Self-concept and Adversity Quotient by Student Independence. The research was conducted in SMP Negeri 44 Surabaya. This study uses quantitative methods. Study sample amounted to 220 students selected using stratified cluster random sampling. Retrieval of data using the three scales, namely self-concept scale, the scale of adversity quotient, and the scale independence of learning. Analysis of the data this study uses multiple regression analysis techniques, with the help of SPSS version 15.0 for Windows. The results of this study found that (1) significant relationship between self-concept and learning self-sufficiency rates obtained with r = 18.199p = 0.000 (p 0.05), (2) there was no significant relationship between adversity quotient to learn independence, prices obtained r = 1, 283 with p = 0.201 (p 0.05), (3) there is a significant relationship between self-concept and adversity quotient, together with the independence of learning, the price obtained F = 166.286 with p = 0.000 (p 0.05). From the analysis of test results obtained also the value of R = 0.778 and R Square = 0.605. This may imply that the independent variables (self-concept and AQ) can explain the dependent variable (independent study) of 60.5%, while the remaining 39.5% which can be explained by factors other causes is not examined. These factors can be either internal factors (originating from within the individual) or external factors (factors that originate from outside the individual).